Analisis Retorika Konten Tiktok Sadam Permana Pada Fenomena Whip Pink Media Sosial - Febby Arie Oktavia (Jurnal Ilmu Sosial dan Humaniora, 2026)
Social media has become a primary medium for disseminating information capable of influencing public perspectives and behaviors, including health-related issues. One phenomenon capturing public attention is Whip Pink, widely discussed across various TikTok content. This study aims to examine the application of Aristotle's rhetorical strategies in TikTok content concerning the Whip Pink phenomenon and to analyze the formation of audience perception toward evolving health issues on social media. The research employs a qualitative approach with a rhetorical analysis method. Data were gathered through observation and documentation of videos, captions, visual elements, and audience interactions within TikTok and Instagram content related to the Whip Pink phenomenon. The analysis is based on ethos, pathos, and logos elements within Aristotle's rhetorical theory. The results indicate that ethos is reflected through the communicator's ability to build audience trust when delivering information. Pathos is evident from the emergence of various emotional responses from the audience, such as curiosity, sympathy, concern, and critical feedback. Meanwhile, logos is observed through the use of rational arguments and explanations to help the audience comprehend the developing issue. The research findings also demonstrate that TikTok serves as a digital health communication space that plays a role in shaping public perception through user interactions. It is suggested for future researchers to expand the research object to other digital platforms to enrich the variation of health communication data.